RIPK2: a promising target for cancer treatment - You, Jieqiong; Wang, Ying; Chen, Haifeng; Jin, Fang (Frontiers in Pharmacology, 2023)
As an essential mediator of inflammation and innate immunity, the receptor-interacting serine/threonine-protein kinase-2 (RIPK2) is responsible for transducing signaling downstream of the intracellular peptidoglycan sensors NOD1/2, which will further activate NF-κB and MAPK pathways, leading to the transcription activation of pro-inflammatory cytokines and productive inflammatory response. Thus, the NOD2-RIPK2 signaling pathway has attracted extensive attention due to its significant role in numerous autoimmune diseases, making pharmacologic RIPK2 inhibition a promising strategy, but little is known about its role outside the immune system. Recently, RIPK2 has been related to tumorigenesis and malignant progression for which there is an urgent need for targeted therapies. Herein, we would like to evaluate the feasibility of RIPK2 being the anti-tumor drug target and summarize the research progress of RIPK2 inhibitors. More importantly, following the above contents, we will analyze the possibility of applying small molecule RIPK2 inhibitors to anti-tumor therapy.